Quality assurance in radiation therapy: study aid; учебно-методическое пособие - Sukhikh E. S. Evgeniya Sergeevna; Sagov I. R. Islam Ruslanovich; Selikhova E. A. Ekaterina Alexandrovna; Stakhova O. M. Olga Mikhailovna (Tomsk, TPU Publishing House, 2025)
Title screen